Representasi Nilai-Nilai Islam dalam Program "Cahaya Tauhid" di MNCTV - Widia Hafifah; Haykal Agastya; Daffa Atha Fairuz Nabiha; Jumroni Jumroni (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to understand how Islamic values are represented in the television program Cahaya Tauhid, broadcast on MNCTV. This program, a religious program, aims to convey moral messages and Islamic teachings through stories related to everyday life. A qualitative approach with a constructivist paradigm was used to explore the representation of Islamic values in this program as a result of social construction influenced by media ideology, the interests involved, and audience responses. Data collected came from non-participant observation of 27 episodes of Cahaya Tauhid broadcast on the MNCTV YouTube Channel. The results show that this program contains Islamic messages that cover five main dimensions: aqidah (faith), worship, morals, social and muamalah (social behavior), and Ramadan spirituality. The most dominant Islamic values in this program are tauhid (monotheism), worship, morals, social and humanitarian, and tazkiyatun nafs (purification of the soul). The values of worship and tauhid, in particular, appear consistently in almost every episode and are the main focus of this program. These messages are delivered in a simple yet meaningful manner, making them easily understood by the audience. This program successfully represents Islamic teachings in the context of everyday life and shapes the audience's perspective on Islam. Thus, Cahaya Tauhid can be considered an example of an effective television da'wah program in building Islamic understanding through mass media, while also serving as a means of education and dissemination of Islamic values. Furthermore, this study also found that Cahaya Tauhid uses a narrative approach that combines Islamic values with real-life stories, making it more relevant and engaging for the audience. Thus, Cahaya Tauhid can be considered an example of an effective television da'wah program in building Islamic understanding through mass media, while also serving as a means of education and dissemination of Islamic values.